THE IMPROVED POWER PROPERTIES OF THE TEST BENCH FOR THE COLLECTOR OF TRACTION ENGINE - Loza, P. O. (Science and Transport Progress, 2008)
In this article the expediency and ways of improvement of power parameters of the test stand for the driving collector motors of locomotives are considered.